Perceived Ease Of Use As An Intervening Factor In Students’ Perceptions Of Learning Outcomes When Completing Assignments Via An AI Chatbot - Rahmawati Erma Standsyah; Raden Sulaiman; Dwi Nur Yunianti; Farhan Halim Sentosa; Nabila Agatha Parsa (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
ABSTRACT   The use of AI-based technologies is increasingly widespread among students, particularly to facilitate assignments and understanding of course materials. Inappropriate use by students can have a negative impact on the future of the country. The objective of this research is therefore to examine the extent to which personal and environmental factors influence students' perceptions of learning outcomes when completing homework, considering the perceived ease of use of Chatbot AI as an intervening construct. In accordance with the TAM and UTAUT frameworks, perceived ease of use acts as an intervening variable that links the influence of personal and environmental factors on learning outcomes. A quantitative methodology, based on SEM-PLS, was used, involving 154 students from SMA/SMK in Surabaya and the surrounding areas. Based on gender, female respondents were 77.9% and male respondents were 22.1%. The validity and reliability of the research instrument were tested. The direct relationship between personal and environmental factors on students' perceived learning outcomes was found to be insignificant (p = 0.277), However, however, each factor is individually significant but the mediating effect is weak and insignificant. This means that students' personal and environmental factors alone do not improve their perception of their learning outcomes, as they feel that the results of AI chatbots do not reflect their own understanding. They consider learning successful only when it involves personal effort. However, when these factors influence perceived ease of use, this ease of use becomes the determining factor in how students evaluate their learning process.